Analysis of marketed soft drinks and reduction of food colours with a simple absorption technique with PVA-Ag nanofilms - Richiepranau Rajkumar; Amritha Varsha Priya Rejith; Kanagavalli Ramasubbu; Devi Rajeswari V (Applied Food Research)
Modern lifestyles, economic growth, and the influences of consuming a diet with high calories, less nutrients, inadequate fibre, and added food colours. These are responsible for causing diseases, like obesity, high blood pressure, diabetes, hypercholesterolemia, heart diseases, stomach ulcers, cancer, and so on. Food-grade dyes added to these foods can cause severe damage to the body, mainly to the gut microbiome, nervous system, liver, kidney, and pancreas. Our study focuses on the food-grade dyes and compounds in the soft drinks available in the market. Soft drinks were analysed with UV–Vis and gas chromatography-mass spectroscopy, Fourier transform infrared spectroscopy and high-performance liquid chromatography. Further, PVA-Ag nanofilms were synthesised and characterised and the soft drinks were incubated with PVA-Ag nanofilm (1 × 1 cm) for three days. The changes in the presence of food-grade dyes were analysed with UV–visible spectroscopy for three consecutive days. In conclusion, chemical compounds and permitted and non-permitted added colours in soft drinks were analysed. Additionally, PVA-Ag nanofilms acted as an excellent absorbent by reducing the dye concentration while increasing the incubation period in soft drinks. This indicates that PVA-Ag nanofilm might reduce the harmful effects of dyes by using the proper absorption technique.